Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1002/2014jd022630
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol impacts on cloud thermodynamic phase change over East Asia observed with CALIPSO and CloudSat measurements

Abstract: Impacts of aerosols on subfreezing cloud thermodynamic phase change over East Asia are studied by using 4 year combined CloudSat radar and Cloud-Aerosol Lidar and Infrared Pathfinder Satellite Observation (CALIPSO) lidar measurements. The mean occurrence frequencies of supercooled-liquid, mixed-phase, and glaciated clouds over East Asia are 10.4%, 10.3%, and 16.9%, respectively. Over northwest of East Asia (32-44°N, 75-100°E), subfreezing clouds are dominated by glaciated clouds with a mean relative cloud frac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 63 publications
2
22
0
Order By: Relevance
“…The six aerosol types include clean marine, smoke (biomass burning), dust, polluted dust (mixtures of dust and smoke), polluted continental, and clean continental [ Omar et al ., , ; Tesche et al ., ]. These CALIPSO data have been widely used by many researchers [ Huang et al ., ; Huang et al ., ; Thorsen and Fu , ; Zhang et al ., ]. This level 2 lidar vertical feature mask product is available online at the NASA Langley Atmospheric Science Data Center website (https://eosweb.…”
Section: Data Set and Methodologymentioning
confidence: 99%
“…The six aerosol types include clean marine, smoke (biomass burning), dust, polluted dust (mixtures of dust and smoke), polluted continental, and clean continental [ Omar et al ., , ; Tesche et al ., ]. These CALIPSO data have been widely used by many researchers [ Huang et al ., ; Huang et al ., ; Thorsen and Fu , ; Zhang et al ., ]. This level 2 lidar vertical feature mask product is available online at the NASA Langley Atmospheric Science Data Center website (https://eosweb.…”
Section: Data Set and Methodologymentioning
confidence: 99%
“…Some studies have investigated the impact of different aerosol types on cold phase clouds over East Asia (Zhang et al, 2015) or at a global scale (Choi et al, 2010;Tan et al, 2014). However, studies of the statistical relationship between cloud phase changes and meteorological parameters have received far less attention, especially at a global scale.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…For example, based on laboratory experiments and field measurements, mineral dust from arid regions has been widely recognized as an important source of IN in mixed-phase clouds because of its nucleation efficiency and abundance in the atmosphere. In addition to dust, some studies have also verified the potential ice nucleation ability of polluted dust and smoke at cold temperatures (Niedermeier et al, 2011;Cziczo et al, 2013;Tan et al, 2014;Zhang et al, 2015). For dynamical process, Naud et al (2006) assessed the impact of large-scale ascent on the cloud phase and found that the areas of greatest large-scale ascent are not glaciated at cloud top as much as areas of moderate ascent.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, studies of cloud thermodynamic phase changes and the vertical structures of mixed and ice‐phase clouds over East Asia from both observations and model simulations are still sparse (Fan et al, ; J. Liu et al, ). The impacts of aerosols on cold‐phase cloud thermodynamic phase changes over East Asia were studied using four years of combined measurements from the CloudSat radar and the Cloud‐Aerosol Lidar and Infrared Pathfinder Satellite Observation (CALIPSO) lidar (Zhang et al, ). Seasonal anomalies of glaciated and mixed‐phase clouds correlate well with the seasonal variations in the frequency of dust occurrence.…”
Section: Impact Of Aerosols On Clouds and Precipitationmentioning
confidence: 99%